The Spending Challenge for Reaching the SDGs in Sub-Saharan Africa : Lessons Learned from Benin and Rwanda - Prady, Delphine (IMF Working Papers; Working Paper, 2019)
This paper documents the additional spending that is required for sub-Saharan Africa (SSA) to achieve meaningful progress in SDGs by 2030. Benin and Rwanda are presented in detail through case studies. The main lessons are: i) average additional spending across SSA is significant, at 19 percent of GDP in 2030; ii) countries must prioritize their development objectives according to their capacity to deliver satisfactory outcomes, iii) financing strategies should articulate multiple sources given the scale of additional spending, and iv) strong national ownership of SDGs is key and should be reflected in long-term development plans and medium-term policy commitments.